Nástroje managementu kvality - Mužík, Lukáš (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2016)
Předmětem této diplomové práce je výběr a implementace nových nástrojů managementu kvality ve vybrané strojírenské společnosti INOX SERVIS s.r.o. V teoretické části jsou analyzovány jednotlivé nástroje a metody managementu kvality, také je zde uveden rozbor současného stavu. Získané informace byly využity při aplikaci nástrojů do výrobního procesu, implementace zhodnocena a následně stanoveny další varianty možného zlepšení procesu.

The subject of this thesis is the selection and implementation of new quality management tools in the selected engineering company INOX SERVIS s.r.o. The theoretical part deals with the different tools and methods of quality management and the analysis of current situation. Obtained information were used in the application of tools in the manufacturing process. Implementation was evaluated and other variants of possible process improvements were established.
Quality Control Tools
Keywords: kvalita; systém managementu kvality; nástroje managementu kvality; FMEA; Quality Assurance Matrix; quality; system of quality management; quality control tool; FMEA; Quality Assurance Matrix